2007
DOI: 10.1111/j.1742-1241.2007.01386.x
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative fluid management: prospective audit

Abstract: Fluid prescription practice in general surgical units is sub-optimal, resulting in avoidable iatrogenic complications. Involvement of senior staff, education and possibly the introduction of prescribing protocols may improve the situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 25 publications
3
48
0
3
Order By: Relevance
“…A CHT infundida do 1º até o 4°dia de pós-operatório foi em média 12,8 [6,[4][5][6][7][8][9][10][11][12][13][14][15][16][17]5] litros. Desse total, 9,5 litros (74,3%) corresponderam a fluidos cristalinos prescritos (CHP) e 3,3 litros (25,7%) a diluentes e medicações venosas.…”
Section: Resultados Resultados Resultados Resultados Resultadosunclassified
“…A CHT infundida do 1º até o 4°dia de pós-operatório foi em média 12,8 [6,[4][5][6][7][8][9][10][11][12][13][14][15][16][17]5] litros. Desse total, 9,5 litros (74,3%) corresponderam a fluidos cristalinos prescritos (CHP) e 3,3 litros (25,7%) a diluentes e medicações venosas.…”
Section: Resultados Resultados Resultados Resultados Resultadosunclassified
“…A telephone survey, 58 two prospective audits, 52,59 and a postal survey of 710 consultant surgeons 57 have confirmed that preregistration house officers (Foundation Year 1 doctors) are commonly made responsible for fluid prescription, but that less than half of them or their SHOs know even the sodium content of "normal" saline. Too few check fluid balance charts regularly, or appreciate for example the need for fluid replacement if bowel preparation is employed.…”
Section: Recommendation 14mentioning
confidence: 98%
“…Even allowing a ±50% tolerance did not improve the score markedly, suggesting most doctors did not even know the approximate electrolyte content of fluids they prescribe.There was no improvement after the introduction of the new fluid prescription chart.This knowledge deficit may have implications for patient outcome. 5 Poor fluid and electrolyte management has been highlighted as a cause of morbidity and mortality,especially in the elderly. 7 In contrast to training for drug prescription, there is little formal training for IV fluid prescription.…”
Section: Discussionmentioning
confidence: 99%
“…4 Fluid-related complications, such as electrolytes imbalance or fluid overload, may occur in up to 54% of patients undergoing major abdominal surgery. 5,6 This is especially so in the elderly and those prescribed excess sodium or fluid volume.This, in turn, leads to a longer hospital stay and unplanned critical care unit admission. It may delay return of gastrointestinal function and contribute to complications such as anastomotic leak.…”
Section: 4mentioning
confidence: 99%